Imperfect Solidarities : Tagore, Gandhi, Du Bois, and the Global Anglophone - Lahiri, Madhumita (FlashPoints (Evanston, Ill.), 2021)
"Imperfect Solidarities: Tagore, Gandhi, Du Bois, and the Global Anglophone theorizes print internationalism, which creates new terms within the worldwide hegemony of the English language to encourage alternate geographies and collectivities"--